2013
DOI: 10.1186/1471-2407-13-388
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of rectal cancer patients improves with downstaging by intensified neoadjuvant radiochemotherapy - a matched pair analysis

Abstract: BackgroundNeoadjuvant radiochemotherapy has been proven superior to adjuvant treatment in reducing the rate of local recurrence without impairing cancer related survival or the incidence of distant metastases in standard protocols of neoadjuvant radiochemotherapy. The present study aimed at addressing the effects of an intensified neoadjuvant radiochemotherapy on long term cancer related and disease free survival.MethodsA total of 387 patients underwent oncologic resection for rectal cancer in our institution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The studies have shown that there is an association between the complete tumor response to neoadjuvant chemoradiation for rectal cancer and the histopathological and genetic characteristics, tumor stage and lymph node involvement (12,13). According to some authors, the tumor local response may be up to 25-40% (13) or even 92.5% in highly-selected cases (14).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…The studies have shown that there is an association between the complete tumor response to neoadjuvant chemoradiation for rectal cancer and the histopathological and genetic characteristics, tumor stage and lymph node involvement (12,13). According to some authors, the tumor local response may be up to 25-40% (13) or even 92.5% in highly-selected cases (14).…”
Section: Discussion Discussionmentioning
confidence: 99%
“…For pretherapeutic clinical staging, a clinical history of the patients was taken and patients had a clinical examination as well as rigid rectoscopy to determine the distance of the lowest tumor border from the anal verge, colonoscopy, endosonographic ultrasound and/or imaging studies of the pelvis (MRI or CT), a CT scan and/or ultrasound examination of the abdomen, liver function tests, and chest X-ray, or CT of the thorax; additional imaging studies were done in the case of suspected metastatic disease. Details of the neoadjuvant therapy and the surgical procedures have been published previously [ 6 ]. Briefly, patients received pelvic radiation of 1.8 Gy single dose five days a week, adding up to 50.4 Gy (years 2000 to 2002; N = 20) or 55.8 Gy (after 2002; N = 84); this was complemented by chemotherapy with 5-FU or capecetabine and irinotecan or oxaliplatin.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we and other working groups have shown that neoadjuvant RCT (nRCT) leads to improved cancer-related survival and disease-free survival on the one hand, but also to more complications and potentially impaired function on the other. 13…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we and other working groups have shown that neoadjuvant RCT (nRCT) leads to improved cancer-related survival and disease-free survival on the one hand, but also to more complications and potentially impaired function on the other. [1][2][3] Endoscopic vacuum therapy (EVT) has become the treatment of choice for anastomotic leaks after rectal resections in various institutions. Suction and drainage via an open-pored polyurethane sponge decrease bacterial contamination, secretion, and local edema.…”
Section: Introductionmentioning
confidence: 99%